2018
DOI: 10.1002/micr.30360
|View full text |Cite
|
Sign up to set email alerts
|

Software‐based video analysis of functional outcomes of face transplantation

Abstract: Software-based video analysis provides a valuable assessment tool capable of objective, precise and reproducible analysis of facial movements and functions after FT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
4
15
0
1
Order By: Relevance
“…Lantieri et al published their long‐term results with their seven patients and showed that when the orbicularis oris muscle recovered, it allowed complete function of the mouth with oral competence 18 . The Boston team has been able to show that mouth opening and smiling functions both improved the most, comparable to those of the normal population 19 . In our two patients, we are able to show good facial and lip muscle recovery similar to previous reports.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lantieri et al published their long‐term results with their seven patients and showed that when the orbicularis oris muscle recovered, it allowed complete function of the mouth with oral competence 18 . The Boston team has been able to show that mouth opening and smiling functions both improved the most, comparable to those of the normal population 19 . In our two patients, we are able to show good facial and lip muscle recovery similar to previous reports.…”
Section: Discussionsupporting
confidence: 84%
“…While some studies report restoration of swallowing after FT, 17,19 there does not appear to be a detailed analysis comparing pre-transplant ability to masticate and swallow to recovery of swallowing after FT. With FT patients, the problems regarding swallowing are usually related to the initial oral phase of swallowing, bolus control, and mastication because the larynx and lower parts of the GI-tract are often unaffected by the initial trauma. Our first patient recovered to practically normal swallowing while the second patient still relies on pureed and liquid-like foods.…”
Section: Swallowingmentioning
confidence: 99%
“…In addition, Nelson et al 27 showed that the use of photographs improved patient care for review of healing or complications in burn therapy. Also, Fischer et al 28 demonstrated video analysis to negotiate inaccuracy and subjectivity in outcome analysis of facial movements and functions after face transplant. Likewise, video allows for transparency in post-ED decision-making, which might be the first step to ensure the quality of care using ED, a quite new method in burn wound care.…”
Section: Discussionmentioning
confidence: 99%
“…Existió una diferencia neta de $26 247 dolares, lo que implica un aumento de 12.7% al recurrir al TF, frente a las técnicas convencionales. Lo anterior teniendo en cuenta, que no se incluyeron los costos asociados a la inmunosupresión de por vida requerida por el paciente 42,43 .…”
Section: Costosunclassified